Birth Plans: What Matters for Birth Experience Satisfaction. Issue 2 (25th February 2016) - Mei, Jenny Y.; Afshar, Yalda; Gregory, Kimberly D.; Kilpatrick, Sarah J.; Esakoff, Tania F.
Abstract: Background: To categorize individual birth plan requests and determine if number of requests and request fulfillment is associated with birth experience satisfaction. Methods: This is a sub‐analysis of a prospective cohort study of 302 women with singleton pregnancies with and without birth plans. Women with a hard copy of their birth plans who completed a postdelivery satisfaction survey were included in this study. We described the number and type of birth plan requests and associated the number of requests and request fulfillment with overall satisfaction, expectations met, and sense of control. Differences between groups were analyzed using chi‐square, Spearman rank correlation, and logistic regression. Results: One hundred and nine women presented to Labor and Delivery with a hard copy of their prewritten birth plan. We identified 23 unique requests. The most common requests were no intravenous analgesia (82%) and exclusive breastfeeding (74%). The requests most fulfilled were avoidance of episiotomy (100%) and no operative vaginal delivery (89%). Having a higher number of requests fulfilled correlated with greater overall satisfaction ( p = 0.03), higher chance of expectations being met ( p < 0.01), and feeling more in control ( p < 0.01). Having a high number of requests was associated with an 80 percent reduction in overall satisfaction with the birth experience ( p < 0.01). Conclusions: Having a higher number of requests fulfilled was positively associated with birth experience satisfaction, while having a high number of requests was inversely associated with birth experience satisfaction. Further research is needed to understand how to improve birth plan–related birth experience satisfaction.